2015
DOI: 10.3389/fncel.2015.00151
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin regulation of synaptic transmission and plasticity: implications for health and disease

Abstract: Thrombin, a serine protease involved in the blood coagulation cascade has been shown to affect neural function following blood-brain barrier breakdown. However, several lines of evidence exist that thrombin is also expressed in the brain under physiological conditions, suggesting an involvement of thrombin in the regulation of normal brain functions. Here, we review ours’ as well as others’ recent work on the role of thrombin in synaptic transmission and plasticity through direct or indirect activation of Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 81 publications
1
64
0
Order By: Relevance
“…In addition, as prothrombin is converted to thrombin upon an enzymatic cleavage by factor X (Ben Shimon et al . ; Stein et al . ), we also measured factor X mRNA levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as prothrombin is converted to thrombin upon an enzymatic cleavage by factor X (Ben Shimon et al . ; Stein et al . ), we also measured factor X mRNA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Novel findings have shown that thrombin is synthesized in the brain with its levels being directly regulated in physiological and pathophysiological conditions (Ben Shimon et al . ). Specifically, upon OGD in vitro , we have found that brain‐derived thrombin rises and alters synaptic plasticity (Stein et al .…”
Section: Discussionmentioning
confidence: 97%
“…In this regard there are numerous anti-inflammatory approaches and, as recently reviewed by Bergold (2015), whereas many have been evaluated in animal models, few have translated to effective clinical development. An interesting agent under recent evaluation by our collaborative group is the small synthetic candidate drug 3,6′-dithiothalamide that inhibits the synthesis of tumor necrosis factor-alpha (TNF- α ) (Zhu et al, 2003; Greig et al, 2004).…”
Section: Pharmaceutical Treatments For Weight Drop-induced Damage mentioning
confidence: 99%
“…The uncovered N -terminal region then acts as a tethered ligand that activates the receptor (Gingrich and Traynelis, 2000). As recently reviewed by Maggio et al (2013a, b) and Ben Shimon et al (2015), PARs are present within the nervous system and whereas PAR-2 acts as a class of trypsin/tryptase-activated receptors, PAR-1, PAR-3, and PAR-4 are most efficiently triggered by thrombin (Gingrich and Traynelis, 2000). Within brain, PAR-1 is expressed on neurons and astrocytes, with stronger immunore-activity evident on astrocytces in human brain – particularly in the hippocampus, cortex, and striatum (Junge et al, 2004).…”
Section: Pharmaceutical Treatments For Weight Drop-induced Damage mentioning
confidence: 99%
“…The signaling mechanisms that drive astrocytes toward a protective versus a toxic phenotype are not fully known (Bao, Hua, Keep, & Xi, ; H. Wang, Ubl, Stricker, & Reiser, ; Y. Wang, Luo, & Reiser, ). Cell–cell signaling via proteases acting on cell‐specific receptors underlies critical mechanistic steps in neurodevelopment and disease (Ben Shimon et al, ; Burda, Radulovic, Yoon, & Scarisbrick, ; De Luca, Virtuoso, Maggio, & Papa, ; Vaughan & Cunningham, ; Wagner et al, ; Yoon, Radulovic, Drucker, Wu, & Scarisbrick, ). The protease activated receptor (PAR), resides in multiple brain cell types, and the majority of PARs are found on astrocytes (Junge et al, ; H. Wang, Ubl, & Reiser, ) and endothelial cells, with lesser densities on neurons, pericytes, and oligodendroglia.…”
Section: Introductionmentioning
confidence: 99%